2015
DOI: 10.2174/15701611113119990005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a New Class of Compounds of the Group of Substituted 5R1, 6H2-1,3,4-thiadiazine-2-amines on the Inflammatory and Cytokine Response in Experimental Myocardial Infarction

Abstract: This study investigated the effects of the L-17 compound of the group of substituted 5R1, 6H2- 1,3,4-thiadiazine-2-amines on the immune response and the plasma level of circulating cytokines in acute myocardial infarction (MI) in rats. The study was based upon experimental work which demonstrated the role of local and systemic inflammatory reactions in MI. Acute MI in rats was induced by left coronary artery coagulation. Histological study of the myocardium sections has been carried out at the 1(th) and 7(th) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…While the stress response and the immune systems are different parts of the larger defensive system [ 10 ], some might discover some immunomodulatory effects, and vice versa. This concept was confirmed by the series of studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and found confirmation in the current studies [ 96 , 97 , 112 ]. Thus, it was found that several chemical compounds of the group of substituted thiadiazines possessed the attributes of atypical antipsychotics, having a significant effect on the behavior of animals and the course of the stress reaction [ 54 , 88 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…While the stress response and the immune systems are different parts of the larger defensive system [ 10 ], some might discover some immunomodulatory effects, and vice versa. This concept was confirmed by the series of studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and found confirmation in the current studies [ 96 , 97 , 112 ]. Thus, it was found that several chemical compounds of the group of substituted thiadiazines possessed the attributes of atypical antipsychotics, having a significant effect on the behavior of animals and the course of the stress reaction [ 54 , 88 ].…”
Section: Discussionsupporting
confidence: 86%
“…Modelling of MI in rats was performed in accordance with the authors’ modification of standard ligation model. Histological, biochemical and immunobiochemical studies were performed at days 1, 5, 7 and 14 of the experiment [ 96 , 97 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the acute onset of AMI and early insensitivity of therapeutic effect evaluation, it is of great importance of identifying the early response in AMI [ 24 ]. At present, serum enzyme indicators are used, including aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and its isoenzymes [ 25 ]. However, AST and LDH are distributed in many organs of the body, and the diagnostic specificity is poor [ 26 ].…”
Section: Discussionmentioning
confidence: 99%